Bile Duct Strictures Caused by Solid Masses: MR in Differential Diagnosis and as a Prognostic Tool to Plan the Endoscopic Treatment. (5th November 2013) - Gorycki, Tomasz; Studniarek, Michał
Abstract : The aim of the study was to assess how realiable is differential diagnosis and prognosis for endoscopic treatment with MR signal characteristics as the qualitative parameter and magnetic resonance cholangiopancreatography (MRCP) images in cases of bile duct obstructions caused by solid masses. Material and Methods . Retrospective study of MR and MRCP images in 80 patients (mean age 58 ys) was conducted. Mean signal intensity ratio (SIR) from planar MR images and MRCP linear measurements were compared between benign and malignant lesions and in groups including the size and number of stents placed during ERCP (< 10 F <) in 51 cases in which ERCP was performed. Results . Significantly higher SIR values were encountered in malignant lesions in T2W images (r = 0, 0003 ) and STIR T2W images (r = 0, 0002 ). Malignant lesions were characterised by longer strictures (r = 0, 0071 ) and greater proximal biliary duct dilatation (r = 0, 0024 ). High significance for predicting ERCP conditions was found with mean SIR in STIR T2W images and stricture length. Conclusion . Probability of malignancy of solid lesions obstructing biliary duct increased with higher SIR in T2W images and with longer strictures. Passing the stricture during ERCP treatment was easier and more probable in cases of shorter strictures caused by lesions with higher SIR in STIR T2W images.